STUDENTS’ DIFFICULTIES IN ORAL PRESENTATION IN CLASSROOM INTERACTION - Nur Annisa; Syarifah Faradiba; Chairil Anwar Korompot (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
This study aimed to find out the following problems: 1) students' difficulties in oral presentations in classroom interaction, 2) how students overcome the difficulties. This study used qualitative research methods.  This study  was  conducted  at  the  Faculty  of  Languages  and  Literatures, Makassar State University using interviews as a data collection instrument. Respondents to this study were 10 English students for the 2022/2023 academic year. Respondents were selected using a random sampling technique. The results of this study indicated that English Education students still face difficulties in oral presentations. The difficulties were classified into 2 categories, namely psychological factors and linguistic factor. Psychological factors consist of (1) anxiety, (2) nervousness, (3) unconfident, (4) understanding the topic, (5) keeping audience’s interest (6) blankness. Difficulties in linguistic factor consist of (1) delivering presentations in English.  The  ways  to  overcome  the  difficulties;  preparing  properly,  taking  deep  breaths, changing mindsets, reducing eye contact in dealing psychology problems, browsing and discussion in dealing understanding of topic, being attractive and interactive in dealing keeping audience interest, practicing English speaking and mixing languages in dealing delivering presentation in English, keep talking in dealing blankness. Keywords: Students Difficulties, Oral Presentation, Classroom Interaction.